2001
DOI: 10.3141/1755-12
|View full text |Cite
|
Sign up to set email alerts
|

Wetting-Induced Settlement of Compacted-Fill Embankments

Abstract: Many highway embankments experience problematic settlements. Compression of soil under the self-weight of the embankment generally occurs during construction, but postconstruction, wetting-induced collapse can result in more long-term settlement problems, depending on climate and movement of the wetting front. A study undertaken to examine settlement associated with unsaturated soil embankments included centrifuge modeling of compacted silt embankments, laboratory testing of the embankment soil, and data inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Thus, the study of the actual hydraulic behaviour of river embankments under simulated high-water events is fundamental to realistically model its mechanical * Corresponding author: roberta.ventini@unina.it response. According to [3], two main mechanisms can cause settlements of compacted fills in partially saturated conditions: self-weight compression and wetting-induced collapse. In the case of compacted soils such as those used for river embankment construction and reinforcement, this last mechanism frequently prevails, resulting in a volumetric collapse, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the study of the actual hydraulic behaviour of river embankments under simulated high-water events is fundamental to realistically model its mechanical * Corresponding author: roberta.ventini@unina.it response. According to [3], two main mechanisms can cause settlements of compacted fills in partially saturated conditions: self-weight compression and wetting-induced collapse. In the case of compacted soils such as those used for river embankment construction and reinforcement, this last mechanism frequently prevails, resulting in a volumetric collapse, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, these cracks may generate water leakage channels and threaten the safety of the structure (Tang et al 2016). There are many factors that significantly influence the deformation induced by wetting such as soil type, ratio of wetting, initial matric suction, degree of saturation, dry unit weight, and stress condition (Miller et al 2001;Lim and Miller 2004;Prakoso 2013;Elsharief et al 2016;and Zheng et al 2017). There are numerous studies concerning the influence of wetting on stress-strain behavior of unsaturated soils (Jennings et al 1962;Kato et al 2000;Ferber et al 2008;AiroFarulla et al 2010;Sun et al 2007;and Bishop 1961).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon potentially exacerbates and weakens the physical and hydraulic performance of structures, subsequently causing settlements and structural deformations ( 2 ). Floodwater and cyclic traffic loads induce internal instability in highway embankments and railway subgrades, resulting in collapses and long-term settlement problems ( 36 ). Also, some forensic studies, for example, Rönnqvist et al ( 7 ) and Stewart and Garner ( 8 ), have reported that internal instability in soils can lead to the formation of sinkholes and piping.…”
mentioning
confidence: 99%
“…This phenomenon potentially exacerbates and weakens the physical and hydraulic performance of structures, subsequently causing settlements and structural deformations (2). Floodwater and cyclic traffic loads induce internal instability in highway embankments and railway subgrades, resulting in collapses and long-term settlement problems (3)(4)(5)(6). Also, some forensic studies, for example, Ro¨nnqvist et al (7) and Stewart and Garner (8), have reported that internal instability in soils can lead to the formation of sinkholes and piping.…”
mentioning
confidence: 99%